IMPLEMENTASI TEKNOLOGI MICRO LEARNING MODULAR SEBAGAI INOVASI STRATEGIS DALAM ADAPTASI PEMBELAJARAN STEM BAGI GENERASI Z - Dede Dwi Kurniasih; Nurul Yusri; Bambang Triawan Pamungkas; Luthfiyah Mahrusah; Muhammad Q Abdan Sholihan; Hasri Nur Azizah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid development of digital technology presents a complex problem in the form of the incompatibility of conventional learning models with the learning characteristics of Generation Z who are digital, multitasking, and require a flexible and interactive approach. This study aims to analyze the implementation of Micro Learning Modular technology as a strategic innovation in adapting STEM (Science, Technology, Engineering, and Mathematics) learning for Generation Z. The research method uses a qualitative approach with a literature review. Data were obtained through analysis of various scientific literature, indexed articles, academic books, and current education policies. Data analysis was carried out using content analysis through theme categorization, theory synthesis, and triangulation of sources and theories to strengthen the validity of the study results. The results show that Micro Learning Modular increases the effectiveness, efficiency, and engagement of students in STEM learning by fragmenting material into small, flexible and interactive units. This approach strengthens students' critical thinking skills, creativity, collaboration, and digital literacy. In addition, this model supports independent learning and personalized learning that is appropriate to the characteristics of Generation Z. However, implementation in Indonesia still faces challenges such as limited teacher digital literacy, technological infrastructure, and suboptimal policy support. The novelty of this research lies in the development of an integrative model that combines STEM principles with Modular Micro Learning strategies digitally and contextually, to build an adaptive, collaborative learning ecosystem aligned with the Golden Indonesia 2045 vision.